The Effect of Project-Based Learning (PjBL) Continuing Learning Innovation on Learning Outcomes of English in Higher Education - Abdul Syakur; Lailatul Musyarofah; Sulistiyaningsih Sulistiyaningsih; Wike Wike (BIRCU, 2020)
The educational approach that emphasizes creative thinking, problem-solving, and interaction is one that is suitable for sustaining this project-based continuous learning. Participation in the current Process, Input, Output, and Outcome is requested of universities. The educational approach that emphasizes creative thinking, problem-solving, and interaction between students and peers in order to create and use knowledge is one that is suitable for sustaining this project-based learning. The aim of this study is to see how continuous learning technologies like PjBL influence the English learning outcomes of students enrolled in Brawijaya University's English Education study programs. The experimental design for this study was a Times-Series System with a Control Group. The one-way ANOVA test was used to analyze the data in this study. The findings showed that the treatment of the TOEFL1test, specifically the pre-and post-test, differed between the contro1 and1experimental groups by using the Project-Based Learning (PjBL) learning model. The experimental class's average pre-test TOEFL score was1344.71, with1a1range of 300-3971and a standard deviation1of129.386. The experimental class's average1post-test1TOEFL score1is 360.83, with a range of values from 303 to 400 and a standard deviation of 24.146. Project-based learning which has a p-value of 0.026, has been shown to improve student's learning outcomes.